2018
DOI: 10.1177/0731684418760205
|View full text |Cite
|
Sign up to set email alerts
|

A review on new mesostructured composite materials: Part II. Characterization and properties of polymer–mesoporous silica nanocomposite

Abstract: Hybrid inorganic–organic materials are promising systems for a variety of applications due to their extraordinary properties with intricate composite architectures composed of nanoscale inorganic moieties with organic polymers synergistically intertwined to provide both useful functionality and mechanical integrity. These materials have a high potential for future applications and therefore attract considerable interest in polymer science research during the last years. Among the various explored inorganic nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 103 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…Recently, the introduction of mesoporous silica for reinforcement in polymer nanocomposites has received a great deal of interest due to the potential to solve the problems of aggregation and poor interfacial interaction [17]. Mesoporous silica has high internal surface area and uniform nanoscale pore sizes which makes them a good candidate for polymer reinforcing and preparation of new polymer nanocomposite materials [18,19]. They present stable 3D framework structures which provide confinement effects of polymer intrusion into nanopores [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the introduction of mesoporous silica for reinforcement in polymer nanocomposites has received a great deal of interest due to the potential to solve the problems of aggregation and poor interfacial interaction [17]. Mesoporous silica has high internal surface area and uniform nanoscale pore sizes which makes them a good candidate for polymer reinforcing and preparation of new polymer nanocomposite materials [18,19]. They present stable 3D framework structures which provide confinement effects of polymer intrusion into nanopores [20].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas platelets (clays and graphene), nanotubes (carbon‐based and others), and nanorods were the first fillers explored in the field of nanocomposites, interest has switched recently to mesoporous aerogel because the belief is that these mesoporous particles can achieve percolation network structure at even lower loadings . Thus, if the reinforcing phase of a binary composite is percolating, then the macroscale properties are optimized .…”
Section: Propertiesmentioning
confidence: 99%
“…[ 15,16 ] While process thermodynamics is governed by factors, such as dope composition and solvent type, the kinetics is related to the substitution rate of solvent and non‐solvent. [ 17,18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] The result showed that the viscosity and storage modulus (G ′ ) of prepared solutions were higher than PES dope solutions using N‐methyl‐2‐pyrrolidone(NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and dimethylacetamide (DMAc). Mousavi et al [ 17,18 ] investigated the effect of solvent power on the viscoelastic behavior of polysulfone (PSF) solutions. They found that the addition of 2P and water to PSF/NMP solution increased the viscoelasticity of dope solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation